Perancangan Sistem Informasi Penyaringan Siswa Baru SMU Menggunakan Php Dan Mysql - Heri Wahyudi (Jurnal Computech & Bisnis (e-Journal), 2013)
School is a place for learning and the educational process should be held election of new students. In the new admissions process will emerge a lot of obstacles in the selection of applicants and entering data into the database. Many schools use manual skills in how to store data. For schools that already have computer equipment still using Microsoft Office Excel and Microsoft Access as the application of new admissions. Submission of information on the number of applicants and selection results are very important and should be accurate. Many new programs are created for new admissions application still stands alone, for it is the author trying to create a program that uses php application which is a programming language based on client and server using a web-service facilities. With the development of systems using the waterfall method, the analysis with data-oriented, its design illustrated in the diagrams DFD (Data Flow Diagram) and implementation using PHP programming language and MySQL database.  Keywords:  systems; filtering; waterfall